Homodiamine-functionalized metal–organic frameworks with a MOF-74-type extended structure for superior selectivity of CO2 over N21. Issue 37 (7th October 2015) - Yeon, Je Seon; Lee, Woo Ram; Kim, Nam Woo; Jo, Hyuna; Lee, Hanyeong; Song, Jeong Hwa; Lim, Kwang Soo; Kang, Dong Won; Seo, Jeong Gil; Moon, Dohyun; Wiers, Brian; Hong, Chang Seop
<x xml:space="preserve">Abstract</x> The functionalized MOFs exhibit exceptional CO2/N2 adsorption capacity and selectivity, associated with the basicity of the introduced amine groups.